SUSTAINABILITY IN PROJECT MANAGEMENT: BEST PRACTICES FOR REDUCING ENVIRONMENTAL IMPACTS IN MEGA PROJECTS - Manchanda, Meera (My University, 2025)
ABSTRACT: Mega projects are contributing to environmental degradation due to their complexity and large scale. Hence, it increases greenhouse gas emissions a lot to the environment. The study critically highlights the integration of sustainability principles in project management methods and focuses on determining the best practices which can reduce the environmental effect on large-scale infrastructure development. The use of a mixed approach helped in combining quantitative and qualitative data together for examining the existing formation for effective strategies like sustainable procurement, modular construction and prefabrication. This study aims to determine the sustainability impact of Balfour Beatty in managing large-scale projects. Modular construction helps in decreasing the energy consumption related to transportation procedures for delivering pre-assembled groups instead of multiple raw resources. Mega projects involve large-scale infrastructure development that causes significant ecological footprints, such as high carbon emissions and excessive resource consumption. The “mixed method of data collection procedure” has been used by the researcher. The data was collected by sharing the questionnaire form that was created in Google form with the selected participants. Participants “who have at least 1 year of experience” in the “construction industry” are selected by the researcher to join and respond to the survey. Therefore “secondary qualitative data” has been collected from multiple sources like academic literatures, research papers, and online articles. A non-randomised sampling method was used by the researcher to collect appropriate data from the participants. Moreover, the findings of the study highlighted that it is crucial to maintain engagement between all the stakeholders and follow early state sustainability planning processes in order to improve the sustainability measures followed by the construction sector. The research contributes a lot to developing green infrastructure and “provides actionable recommendations” for all the project managers to follow the construction process in a proper way for developing the environmental condition. Moreover, future research can be done by collecting qualitative information from primary sources. Interview sessions with all the workers in the construction sites can help in identifying the practical challenges they face and provide better insights about the research topic. Modular construction reduces the energy required to transport excess materials. Production of pre-fabricated materials in factories helps achieve better control over insulation installation. Balfour Beatty involves rating systems to benchmark their performance. The sustainability initiative of the organisation is comprehensive. It encompasses governance, social, and environmental aspects. Companies need to use green construction practices by following modular construction and prefabrication methods.
Keywords: construction industry; sustainable development; construction; environmental effects; construction sector; ecological construction; projects; energy efficiency; modular construction; project leadership; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Management; Strategic Project Management